LUMINIDEPENDENS orchestrates global transcriptional repression in Arabidopsis - Clara Bergis-Ser; Qingyi Wang; Xiaoning He; Maherun Nisa; Vickie Kaiser; Christelle Mazubert; Jeannine Drouin-Wahbi; Rim Brik-Chaouche; Layla Chmaiss; Jelle Van Leene; Geert De Jaeger; Jose Gutierrez-Marcos; et al. (Proceedings of the National Academy of Sciences, 2025)
Genomic integrity is constantly challenged by transcription/replication conflicts, a major source of replication stress and instability across all life forms. While extensive studies have elucidated mechanisms for resolving transcription/replication conflicts in animals, yeast, and prokaryotes, their counterparts in plants remain largely unexplored. Through a forward genetic screen, we identified LUMINIDEPENDENS (LD), previously known for its role in regulating the flowering repressor FLC , as a key factor in mitigating replication stress in plants. Notably, transcriptomic analyses reveal that LD loss results in the upregulation of over half of the Arabidopsis genes, placing LD as a global transcriptional repressor. Consistent with this role, LD directly binds a substantial portion of the Arabidopsis genome and interacts with the MED18 subunit of the Mediator complex to modulate RNA polymerase II phosphorylation. These findings uncover a fundamental function of LD in fine-tuning transcription at a genome-wide scale, with potentially an additional role in suppressing transcription–replication conflicts by locally dampening transcription and promoting replication fork progression. Our work highlights an intriguing genome-protective strategy in plants, that could shed light on mechanisms involved in transcription–replication conflict management in eukaryotic systems.